DIMENSI BUDAYA INDIVIDUALISM-COLLECTIVISM PADA EKSPATRIAT (TENAGA KERJA ASING) DALAM INDUSTRI PERHOTELAN DI BALI - Dewi, Ni Gusti Ayu Susrami; Dariwardani, Ni Made Inna (Institut Agama Hindu Negeri Gde Puda Mataram, 2023)
Tourism is one sector that generates a lot of labor migration, both between countries and between regions. Bali as one of Indonesia's tourism centers, has a number of foreign nationals or expatriates who work especially in the hotel industry and generally they are at the managerial level. This study examines the extent of the implications of the individualism-collectivism cultural dimension of Hofstede (1980) on expatriates in the hotel industry and how they can adapt to these cultural differences. A comparative analysis of the Individualism-Collectivism Index (IDV) from the countries of origin of the expatriates was carried out to be compared with Indonesia's IDV values ​​as an approach to Bali's IDV values ​​which are presented descriptively based on a study of literature. A significant difference was found between the Bali IDV values ​​and the IDV values ​​of the countries of origin of the expatriates, especially western countries such as the United States, Australia and the United Kingdom which have high IDV values ​​(more than 50) indicating that their cultural dimensions are more individualism, while Indonesia's IDV value including Bali is low as a reflection of collectivism culture. Thus, expatriates assigned to hotels in Bali who come from countries with individualistic characteristics should adapt to the characteristics of local employees in Bali who tend to be collective by implementing collectivism characteristics in their human resource management, namely group performance based.